Association between drug use and ART use among people living with HIV who inject drugs in Vietnam, Ukraine and Indonesia: results from HPTN 074. (2nd November 2022) - Ha, Tran Viet; Hoffman, Irving F.; Miller, William C.; Mollan, Katie R.; Lancaster, Kathryn E.; Richardson, Paul; Zeziulin, Oleksandr; Djoerban, Zubairi; Sripaipan, Teerada; Chu, Viet Anh; Guo, Xu; Hanscom, Brett; et al.
ABSTRACT: Background and objective: Drug use type and frequency may affect Anti-Retroviral Therapy (ART) uptake for HIV-infected people who inject drugs (PWID). This paper assesses the association between self-reported baseline drug use and ART among HIV-infected PWID in Indonesia, Ukraine and Vietnam. Methods: Data on self-reported baseline drug use and ART among HIV-infected PWID at the 26- and 52-week follow-ups were extracted from the HIV Prevention Trials Network (HPTN) 074, a randomized, controlled vanguard study to facilitate HIV treatment for PWID in Indonesia, Ukraine, and Vietnam. Multivariable logistic regression models were fit by study site and the whole HPTN 074 sample, using a 0.5 type I error rate. Results: The response rate were 83.3% and 77.0% at 26 th and 52 th weeks. At 26-week, baseline use of over one non-opiate/non-stimulant drug was associated with lower odds of ART use among Indonesian participants (OR = 0.21, 95%CI: 0.05–0.82); and baseline injecting drugs for over 20 days in the previous month was associated with lower odds of ART use among all HPTN 074 sample (OR = 0.59, 95% CI: 0.36–0.97). Conclusion: The association of a specific drug use pattern with later ART uptake implies the importance of medication-assisted treatment to enhance ART uptake and adherence among participants.